Growth and Convergence in the Central and East European Countries towards EU /1992-2002/ - Aleksandar Vasilev (Economics Department, American University in Bulgaria, 2004)
The main focus of the paper is the growth process in transition countries in the period 1992-2002, by taking the production function approach. The empirical crosssection study performed found that initial life expectancy and net savings speed up growth while death rate, inflation, and terms of trade hamper the increase in GDP. The paper also aims at policy implications, such as better spending in the legal system, health care and social security could help governments foster the restructuring process and decrease the effect of the mistakes done in the past.
Keywords: C01; 330; growth; transition countries